An analysis of the co-operation between the Office of the Auditor-General and provincial departments in the promotion of effective public accountability in the Northern Province - Nevhutalu, Muvhango Lawrence (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA) -- University of Stellenbosch, 1999.